Influence of soil pH on microbial community and incidence of Basal Stem Rot (BSR) disease development in oil palm seedlings planted on BSR affected and forest soils - Rahman, Khunaw Abdulla (2017)
Basal stem rot (BSR) disease caused by Ganoderma boninense, remains as the most challenging disease in oil palm industry. In search for a practical approach to halt Ganoderma incidence and development in oil palm plantations, experiments were conducted with the following objectives; (i) to evaluate the diversity of microbial communities in BSR affected oil palm and forest soils, (ii) to determine the role of indigenous microbial community in suppressing the development of G. boninense in oil palm seedlings, (iii) to determine the effect of soil pH on growth of oil palm seedlings and BSR disease development in Ganoderma inoculated seedlings, and (vi) to evaluate the influence of pH and calcium ion in soil amended with liming material on Ganoderma development in the roots of oil palm seedlings. Four seperate experiments were conducted under laboratory and glasshouse conditions. Soil samples from three different oil palm locations (BSR affected, unaffected and forest) were collected and analyzed for physicochemical properties, the microbial biomass carbon and total microbial enzyme at different depths. Metagenomic determination of soil bacterial diversity in Ganoderma affected and unaffected soils was also dertemined (Experiment 1). Soil sterilization technique was used to eliminate the presence of indigenous microorganisms in the three different soils. Rubber wood blocks fully colonized with G. boninense UPM13 mycelium were used to inoculate 3-month old oil palm seedlings. Seedlings with (G+) and without (G-) Ganoderma inoculation were then grown in the respective soils for four months. Plant growth (shoot and root dry weights), nutrient uptake, soil microbial properties, disease incidence (DI) and disease severity index (DSI) were determined at harvest (Experiment 2). Soil from BSR affected soil of pH 4.5 was adjusted with liming material, calcium carbonate (CaCO3) to pH 5, 6, and 7. Oil palm seedlings were then grown with (G+) and without without (G-) Ganoderma inoculation. Plant growth and disease incidence were determined as in Experiment 2 (Experiment 3). Acid washed sand culture was adjusted with CaCO3 to pH 5, pH 6 and pH 7 were each applied with four levels of calcium (0, 0.27, 0.40 and 0.60 g Ca/pot) using CaCl2 as the calcium source. Oil palm seedlings were grown with and without Ganoderma inoculation. Plant growth and disease incidence were determined as in Experiment 2 (Experiment 4). Results of Experiment 1 showed that the populations of bacteria, fungi, and actinomycetes in BSR affected, unaffected and forest soils significantly (P ≤ 0.05) decreased with increased in soil depth. The observed pattern corresponded with the microbial biomass carbon with the highest value in forest soil. The total microbial enzymes showed decreasing trend with increasing depth, with higher values in forest and BSR unaffected soils. The BSR unaffected soil had the highest relative abundance of Acidobacteria and Actinobacteria compared to other bacterial groups. Both of the bacteria phyla relative abundance exhibited a strong link with soil pH and total carbon. Results of Experiment 2 showed that sterilized soil without presence of indigenous microbial community gave lower plant growth and higher disease incidence. Seedlings grown in nonsterilized and non-Ganoderma inoculated forest soil had the highest (P ≤ 0.05) shoot and root biomass as well as root length, root surface area and root tips number. Mean while, seedlings grown in non-sterilized and non-Ganoderma inoculated BSR affected soil had the lowest plant biomass. Higher bacterial populations were observed in the forest soil compared to BSR affected and unaffected soils. Seedlings grown on forest soil showed better growth with lower DI and DSI and having the highest uptake of N (724 mg/plant), P (60 mg/plant) and K (605 mg/plant) compared to others treaments. Experiment 3 showed that the non-Ganoderma inoculated seedlings of pH 6 + Gdisplayed higher top biomass (8.46 %) and highest root growth. Seedlings grown at higher pH of 7 had lower shoot growth compared to that with Ganoderma inoculation. Ganoderma infected seedlings at pH 5 had the lowest growth. The DI and DSI of seedlings with Ganoderma inoculation pH 5 were higher that at other pH. The Ganoderma (G+) treated plants displayed lower populations of bacteria, fungi, and actinomycetes than without Ganoderma treated groups at all pH levels, though pH 6 + G- soil had the highest bacterial population. Higher nutrient contents, chlorophyll and photosynthesis were observed in plants without Ganoderma inoculation as compared to that with Ganoderma. The highest shoot N and Ca were observed at pH 6 while the P, K and Mg at pH 5. Experiment 4 showed that addition of Ca to non- Ganoderma inoculated seedlings resulted in higher shoot and root biomass with highest yields observed at pH 6 G- (Ca 0.27). Addition of higher Ca (0.6 Ca/pot) increased root length, surface area, and volume (2.99, 3.24 and 2.34 %, respectively) and the bole size compared to at other pH. Higher lignin content of Ganoderma infected plants were oberved at pH 6 G+ Ca (0.60) compared to at pH 4.5. The pH 6 together with 0.6 Ca g/pot application significantly reduced the disease infection in Ganoderma affected seedlings and improved biomass yield and activity of indigenous microorganisms. Under controlled condition, pH 6 with addition of Ca appeared to be effective in controlling BSR disease in oil palm seedlings.